2006
DOI: 10.1523/jneurosci.0294-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Nitric Oxide Synthase Plays a Key Role in CNS Demyelination

Abstract: Nitric oxide (NO) is a small, short-lived molecule released from a variety of cells that is implicated in a multitude of biological processes.In pathological conditions, overproduction of NO may lead to the generation of highly reactive species, such as peroxynitrite and stable nitrosothiols, that may cause irreversible cell damage. Accordingly, several studies have suggested that NO may be involved in the pathogenesis of various neuroinflammatory/degenerative diseases. Increased concentrations of NO in the CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 50 publications
2
52
0
2
Order By: Relevance
“…E: Galectin 3 mRNA was gradually upregulated in microglia in the course of demyelination and remyelination, became detectable at the protein level at 5WD (data not shown), and remained upregulated up to 2WR (5WD, 5 weeks of demyelination; 1WR, 1 week of remyelination; 2WR, 2 weeks of remyelination; Tgfb, transforming growth factor beta; Spp1, osteopontin; Iba1, ionized calcium-binding adaptor molecule 1; IB4, isolectin B4; Slpi, antileukoproteinase; Cd11c, integrin alpha-X, a dendritic cell marker; Gal3, galectin-3; calibration bars in our study, both of which have been shown to be indispensable for remyelination to occur (Arnett et al, 2001;Mason et al, 2001). Interestingly, inducible nitric oxide synthase (iNOS) was found to be induced in the cuprizone model in microglia (Arnett et al, 2002;Liñares et al, 2006) and was moderately protective against demyelination (Arnett et al, 2002). Nonetheless, iNOS was not among the genes expressed in our study.…”
Section: Discussionsupporting
confidence: 53%
“…E: Galectin 3 mRNA was gradually upregulated in microglia in the course of demyelination and remyelination, became detectable at the protein level at 5WD (data not shown), and remained upregulated up to 2WR (5WD, 5 weeks of demyelination; 1WR, 1 week of remyelination; 2WR, 2 weeks of remyelination; Tgfb, transforming growth factor beta; Spp1, osteopontin; Iba1, ionized calcium-binding adaptor molecule 1; IB4, isolectin B4; Slpi, antileukoproteinase; Cd11c, integrin alpha-X, a dendritic cell marker; Gal3, galectin-3; calibration bars in our study, both of which have been shown to be indispensable for remyelination to occur (Arnett et al, 2001;Mason et al, 2001). Interestingly, inducible nitric oxide synthase (iNOS) was found to be induced in the cuprizone model in microglia (Arnett et al, 2002;Liñares et al, 2006) and was moderately protective against demyelination (Arnett et al, 2002). Nonetheless, iNOS was not among the genes expressed in our study.…”
Section: Discussionsupporting
confidence: 53%
“…Previous results demonstrate that demyelination was mainly prevented in mice lacking nNOS. In eNOS -/-mice, demyelination increased to the same level as in wild type, but they showed a slight delay in spontaneous remyelination [50].…”
Section: Role Of Nnos In Neurodegenerationmentioning
confidence: 79%
“…The constitutive NOS make the cuprizone-induced model of demyelination/remyelination [50]. Previous results demonstrate that demyelination was mainly prevented in mice lacking nNOS.…”
Section: Role Of Nnos In Neurodegenerationmentioning
confidence: 99%
“…[28] These effects may be attributed to an increase in different isoforms of NOS all of which may lead to detrimental effects. [29] It may thus be inferred from this study that there may be different effects of administration of pramiracetam in different test organisms and may thus need further study to verify whether adverse effects may be seen or not. Furthermore, without conclusive evidence on the effect of pramiracetam, careful use of the nootropic is warranted.…”
Section: Discussionmentioning
confidence: 91%